2004
DOI: 10.1093/intimm/dxh051
|View full text |Cite
|
Sign up to set email alerts
|

Early events associated to the oral co-administration of type II collagen and chitosan: induction of anti-inflammatory cytokines

Abstract: Oral administration of an antigen can result in local and systemic priming or tolerance and the basis of this dichotomy is poorly understood. The intestinal microenvironment, and factors such as nature of the antigen, dose, genetic background, uptake and concentration of the antigen that gain access to the internal milieu via the mucosa influence these active immunologic processes. Chitosan is a biocompatible natural polysaccharide able to promote the transmucosal absorption of peptides and proteins. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 43 publications
6
28
0
Order By: Relevance
“…Interestingly, while the sustained contact of CII or CII : chitosan with the mucosal immune system generated specific tolerance, chitosan itself produced some effect on B cell function. We cannot explain this finding fully, although the result is in agreement with our previous reports showing that chitosan conditions, after sustained administration, an anti‐inflammatory environment at the inductive mucosal sites [21,22]. Recently, novel and remarkable activities of polysaccharides on mucosal immunity have been described that include the settlement of the T cell repertoire and the release of IL‐10 [41,42].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, while the sustained contact of CII or CII : chitosan with the mucosal immune system generated specific tolerance, chitosan itself produced some effect on B cell function. We cannot explain this finding fully, although the result is in agreement with our previous reports showing that chitosan conditions, after sustained administration, an anti‐inflammatory environment at the inductive mucosal sites [21,22]. Recently, novel and remarkable activities of polysaccharides on mucosal immunity have been described that include the settlement of the T cell repertoire and the release of IL‐10 [41,42].…”
Section: Discussionsupporting
confidence: 77%
“…We have demonstrated that oral administration of chitosan triggers the recruitment of immature dendritic cells [22], up‐regulates IL‐4 and TGF‐β mRNA expression [21,22], reduces IL‐2 levels and increases specific IL‐10 release [21] at the inductive mucosal sites. Considering that most of these factors have been associated with the induction of regulatory subpopulations [21,22,30,37,38], we evaluated the occurrence of T cells with regulatory characteristics. Upon restimulation in vitro with the relevant antigen, both the diluent and chitosan groups showed similar percentages of CD4 + IL‐10 + cells in lymph nodes or spleen (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-␣, IL-4, and IL-12 (4 g) and TGF-␤ (2 g) of total RNA were incubated with 0.5 g oligo(dT; Biodynamics, Buenos Aires, Argentina) for 5 min at 70°C and allowed to stand on ice for 5 min. [24]. Each sample was incubated in a thermal cycler (PTC-100 thermal cycler, M.J. Research, Watertown, MA) using one cycle at 94°C for 5 min; this was followed by 25 cycles for ␤-actin, 30 cycles for IL-4, or 35 cycles for TGF-␤, TNF-␣, and IL-12; each cycle consisted of 1 min at 94°C, 1 min at 55°C (␤-actin, TNF-␣, and IL-12) or 58°C (TGF-␤ and IL-4), and 1 min at 72°C, with a final extension at 72°C for 5 min.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…29, 30 These amine groups have been described to reversibly destabilize cell plasma membrane, 31 which enhances uptake of cargo co-administered with chitosan. 32 In addition, when orally administered to mice, chitosan is transported primarily associated with DCs or macrophages to LNs that drain the gastrointestinal mucosa. 18 In the present study, it is conceivable that chitosan opens tight junctions of the vaginal epithelium to facilitate NP transepithelial delivery while also promoting greater association between NPs and cells locally in the RT to cause accumulation distally in the dLNs.…”
Section: Discussionmentioning
confidence: 99%